Report of the Working Group on Occupational Safety and Health for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The Constitution of India has specific provisions for ensuring OSH for workers in the form the three Articles 24, 39 (e and f) and 42. The statutes relating to OSH are broadly divided into three- statutes for safety at workplaces (e.g. Factories Act, 1948 and Mines Act, 1952), statutes for safety of substances (e.g. Indian Explosives Act, 1884), and statutes for safety of activities (e.g. Radiation Protection rules under the Atomic Energy Act). The terms of reference for the present report covers OSH aspects relating to safety at workplace
Government of India Planning Commission
Government of India Planning Commission